2017
DOI: 10.4174/astr.2017.92.6.402
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of the tacrolimus and cyclosporine A on the colon anastomosis recovery of rats

Abstract: PurposeThis study aims to examine and compare the effects of immunosuppressant cyclosporine A (CsA) and tacrolimus (TAC) on colon anastomosis recovery.MethodsForty rats were randomly divided into 4 groups. The 4 groups were determined as follows: control group; sham group, given %0.09 NaCl; TAC group, given 0.5 mg/kg/day tacrolimus; and CsA group, given 5 mg/kg/day CsA. A 6-cm midabdomen incision was performed on the rats. An incision of all layers on the right colon was performed. Then anastomosis was underta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…There were statistically significant differences among bursting pressures of groups (P<0.001). The value was significantly lower in tacrolimus group compared to control group (P<0.001) [24].…”
Section: хирургическая гастроэнтерология Surgical Gastroenterologymentioning
confidence: 77%
See 2 more Smart Citations
“…There were statistically significant differences among bursting pressures of groups (P<0.001). The value was significantly lower in tacrolimus group compared to control group (P<0.001) [24].…”
Section: хирургическая гастроэнтерология Surgical Gastroenterologymentioning
confidence: 77%
“…According to their investigations preoperative serum protein was the only independent risk factor for anastomotic failure (p<0.0001, OR 0.6 per g/dL) [ 2021) have demonstrated some medication use may affect the development of AL. According to their study results the use of corticosteroids and some immunosuppressive medicines may delay and impair anastomotic healing [14,24,25].…”
Section: хирургическая гастроэнтерология Surgical Gastroenterologymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common complications is anastomotic leak, which leads to high morbidity and mortality rates. Therefore, anastomotic leak has been one of the most investigated topics in colorectal surgery 11 , 24 . In the literature, there are experimental studies on anastomotic healing which involve methods such as reducing the number of sutures, dexpanthenol, coenzyme Q10, krill oil, and fish oil 3 , 6 , 9 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Benacerraf et al [ 5 , 6 ] pointed out that the anastomosis leakage risk rate was almost 100% in cases where perianastomotic tissue oxygen pressure levels dropped below 20 mm-Hg, and the rate of anastomotic leakage decreased with increases in oxygen pressure [ 5 , 6 ]. Therefore, anastomotic leaks after intestinal, colonic, and colorectal anastomosis surgery continue to be an important problem today [ 7 , 8 ]. Although the number of studies aimed at preventing or reducing ischemic damage in colon anastomosis has increased in recent years, as far as we know, no research has been found in the literature investigating the effects of dexpanthenol or coenzyme Q10 (CoQ10) administration on the healing of ischemic colonic anastomosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%